The effectiveness of the training courses conducted by Institute Management Malacca / Mazura Mokhtar - Mokhtar, Mazura (Faculty of Business and Management, 2006)
This study was concentrated on the observation of the effectiveness of the training courses conducted by Institute of Management Malacca. This study was carried out at Malacca and focused on the past participants who have attended the training program at least once. The study also looked at several factors that can influence the effectiveness of the training courses. The factors include trainers-centered factors; organizationcentered factors include module, objective, content and schedule of the training program, and facilities. Nowadays, training becomes more important to many businesses and industries. Most of them realized that providing training to employees will give back many benefit to them and to adapt to any changes in environment. By sending their employees to training they can improve quality of work, and skills, get more knowledge, and get a clear view about their career or tasks. So, it is important to evaluate the effectiveness of the training program in order to know whether their employees motivated during the course. This is an exploratory research and the method used was probability sampling that is simple random sampling. For collecting the data, primary data was used include questionnaires and personal interview and secondary data was used in order to support primary data. Before an actual survey has been done, pilot study was carried out to identifying and eliminating potential problems. Then the actual survey was carried out on 2th March to 10th April 2006. After that, the data was collected and analyzed by using Statistical Package for Social Science (SPSS). All the objectives of the research were answered by using frequency analysis. Besides that, in order to support the findings. the data also has been analyzed by cross-tabulation. It is to know the relationship between gender and total effectiveness. Lastly, at the end of the study it has concluded that the training course conducted by IMM was very effective and most of the participants of the course satisfied with the training program. Also, I have recommended some suggestion to be improved. This is beneficial to IMM to improve their services in order to achieve its vision and mission.